Catalytic Hydroconversion of Lauric Acid Over Poly(N-vinyl-2-pyrrolidone)-Coated Pd Nanoparticles on ZIF-8 - Dahnum, Deliana; Ramadhita, Holanda; Andreas, Andreas; Prasetyo, Joni; Bakti, Aditia Nur; Dang, Huyen Tran (Bulletin of Chemical Reaction Engineering & Catalysis, 2024)
A subclass of Metal-Organic Frameworks, Zeolitic Imidazole Frameworks-8 (ZIF-8) is known as an emerging material that has the characteristic of a large surface area, good thermal stability as well as a high porosity. Instead of having extraordinary properties, ZIF-8 consists of Lewis acid and Lewis base site on its Zn metals and 2-methylimidazole which are the important components for the catalyst. In this study, Pd-Poly(N-vinyl-2-pyrrolidone) coated on ZIF-8 (Pd-PVP@ZIF-8) was synthesized by mixed Pd-PVP solution and ZIF-8 precursors at room temperature. The Pd-PVP solution was varied from 10 to 50 ml to differentiate the Pd concentration in ZIF-8. As-synthesized 50 ml of Pd-PVP on ZIF-8 (50Pd-PVP@ZIF-8) showed catalytic activity in the conversion of 98.6% lauric acid to produce 78.2% of 1-dodecanol at optimum condition 320 °C for 6 h. The synergy between Pd-PVP as metal and ZIF-8 as metal support as well as high dispersion of Pd particles could enhance performance in the conversion of lauric acid. Copyright © 2024 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).